LEGAL REGULATION OF CHILDREN’S CAMPS (CENTER) IN UKRAINE - Narovlianskyi, Oleksandr D. (Educological discourse, 2014)
This article analyzes the history and current state of the regulatory system of legal regulation of children (up to 1991 - Pioneer ) camps and centers. Advisability study determined the need to improve the regulatory framework and accounting historical opytadlya solutions to existing problems . The article analyzes the processes of formation of the regulatory framework of children’s camps in the Ukraine in the period from 1922 to the present. The main problems associated with prolonged uncertainty of the status of these institutions. Ways of improving the existing regulatory framework of children’s centers.